Making legal history : essays in honor of William E. Nelson - Nelson, William E. (William Edward), 1940-; Hulsebosch, Daniel Joseph; Bernstein, Richard B., 1956- (New York : New York University Press, 2016)
For more than four decades, Nelson has produced some of the most original and creative work on American constitutional and legal history. His prize-winning books have blazed new trails for historians with their substantive arguments and the scope and depth of Nelson's exploration of primary sources. Nelson was the first legal scholar to use early American county court records as sources of legal and social history, and his work (on legal history in England, colonial America, and New York) has been a model for generations of legal historians. This book includes a number of chapters exemplifying and explaining the process of identifying and interpreting archival sources-the foundation of an array of methods of writing American legal history.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Law -- United States -- History; Law; United States of America, USA; History of the Americas; Jurisprudence & general issues; Legal history; Laws of specific jurisdictions & specific areas of law